2013
DOI: 10.1073/pnas.1314702110
|View full text |Cite
|
Sign up to set email alerts
|

The king cobra genome reveals dynamic gene evolution and adaptation in the snake venom system

Abstract: Significance Snake venoms are toxic protein cocktails used for prey capture. To investigate the evolution of these complex biological weapon systems, we sequenced the genome of a venomous snake, the king cobra, and assessed the composition of venom gland expressed genes, small RNAs, and secreted venom proteins. We show that regulatory components of the venom secretory system may have evolved from a pancreatic origin and that venom toxin genes were co-opted by distinct genomic mechanisms. After co-opt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

30
428
2
7

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 433 publications
(478 citation statements)
references
References 58 publications
30
428
2
7
Order By: Relevance
“…S15). These results are perhaps unsurprising, but they further reflect the apparent distinction between pathogenically important toxin families (e.g., SVMP and SP) and so-called "ancillary" toxin families (e.g., LAAO and CRISP) described (15). Here, we demonstrate that this dichotomy appears to extend from the mode and tempo of gene family evolution noted (15) to the mechanisms governing toxin transcription and translation.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…S15). These results are perhaps unsurprising, but they further reflect the apparent distinction between pathogenically important toxin families (e.g., SVMP and SP) and so-called "ancillary" toxin families (e.g., LAAO and CRISP) described (15). Here, we demonstrate that this dichotomy appears to extend from the mode and tempo of gene family evolution noted (15) to the mechanisms governing toxin transcription and translation.…”
Section: Resultssupporting
confidence: 52%
“…Typically, toxins are encoded by relatively few (approximately 5-10) multilocus gene families, with each family capable of producing related isoforms generated by gene duplication events occurring over evolutionary time (1,14,15). The birth and death model of gene evolution (16) is frequently invoked as the mechanism giving rise to venom gene paralogs, with evidence that natural selection acting on surface exposed residues of the resulting gene duplicates facilitates subfunctionalization/neofunctionalization of the encoded proteins (15,(17)(18)(19). The result of these processes is a complex suite of toxins that act synergistically to cause rapid prey death.…”
mentioning
confidence: 99%
“…Recent proteomic and genomic investigations of snake venom toxins have indicated that toxin genes are important for capturing prey and have been massively expanded by variable levels of gene duplication, resulting in protein neofunctionalization with directional selection (14). However, the exact molecular interactions involved in these fast evolving toxin homologues at the cellular level have not been addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent genomic investigation of the King cobra has indicated that dynamic gene evolution and adaptation actually is in operation in the snake venom system (14). For the fast evolving biological weapon systems such as snake toxins, a comparative structural and functional study of naturally abundant CTX homologues should shed light on how venom proteins evolve at the molecular and cellular levels.…”
mentioning
confidence: 99%
“…However, it could be a vestige of the pancreatic origin of the venom gland (30). These snake venom AChEs are inhibited by small, organic PAS ligands such as propidium, albeit at a lower affinity compared with the other species found in neuronal or neuromuscular tissues, but they differ widely in their sensitivity to larger, peptidic PAS ligands such as Fas2 or mAb Elec410 (see below) (27,31,32).…”
mentioning
confidence: 99%